2011
DOI: 10.1016/j.exppara.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Babesia gibsoni: Detection in blood smears and formalin-fixed, paraffin-embedded tissues using deoxyribonucleic acid in situ hybridization analysis

Abstract: In the present study, we attempted to detect Babesia gibsoni in blood smears and formalin-fixed, paraffin-embedded tissues obtained from B.gibsoni-infected dogs using in situ hybridization. Using a digoxigenin-conjugated deoxyribonucleic acid (DNA) probe, both intraerythrocytic and exoerythrocytic parasites in the culture could be specifically stained in blood smears fixed with 4% phosphate-buffered paraformaldehyde. This indicated that genomic DNA extracted from the parasites could be detected using in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…(Yamasaki et al . ). For ISH analysis, blood smears were formalin‐fixed and paraffin‐embedded before mounting on Probe‐On Plus slides (Fisher Scientific).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…(Yamasaki et al . ). For ISH analysis, blood smears were formalin‐fixed and paraffin‐embedded before mounting on Probe‐On Plus slides (Fisher Scientific).…”
Section: Introductionmentioning
confidence: 97%
“…The quantitative real-time PCR for CyHV-2 titration, tissue section preparation and ISH analysis were performed as described previously (Xu et al 2014). Peripheral blood smears were prepared as described by Masahiro et al (Yamasaki et al 2011). For ISH analysis, blood smears were formalin-fixed and paraffin-embedded before mounting on Probe-On Plus slides (Fisher Scientific).…”
Section: Introductionmentioning
confidence: 99%
“…In Beagle dogs experimentally infected with B. gibsoni , it was possible to detect the parasites with a probe matching a 516 bp DNA fragment of the heat-shock protein 70 (BgHsp70) gene via ISH. 73 FISH is available for the detection of other Babesia spp. ( B. duncani , B. microti ) in fresh human 61 and hamster blood smears.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that mtDNa should not be deeply involved in Da resistance in B. gibsoni. Babesia gibsoni is a blood protozoan of dogs and a causative pathogen of canine babesiosis [34]. It is difficult to eliminate this parasite from infected dogs, although a number of drugs, including diminazene aceturate (Da), clindamycin, metronidazole, pentamidine, and atovaquone combined with azithromycin, are used for treatment of the disease [9,16,22,29].…”
mentioning
confidence: 99%